Environmental sustainability in orthopaedic surgery <subtitle>a scoping review</subtitle> - Kar May Phoon; Irrum Afzal; David H. Sochart; Vipin Asopa; Panagiotis Gikas; Deiary Kader (Bone & Joint Open, 2022)
AimsIn the UK, the NHS generates an estimated 25 megatonnes of carbon dioxide equivalents (4% to 5% of the nation’s total carbon emissions) and produces over 500,000 tonnes of waste annually. There is limited evidence demonstrating the principles of sustainability and its benefits within orthopaedic surgery. The primary aim of this study was to analyze the environmental impact of orthopaedic surgery and the environmentally sustainable initiatives undertaken to address this. The secondary aim of this study was to describe the barriers to making sustainable changes within orthopaedic surgery.MethodsA literature search was performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines through EMBASE, Medline, and PubMed libraries using two domains of terms: “orthopaedic surgery” and “environmental sustainability”.ResultsA total of 13 studies were included in the final analysis. All papers studied the environmental impact of orthopaedic surgery in one of three areas: waste management, resource consumption, and carbon emissions. Waste segregation was a prevalent issue and described by nine studies, with up to 74.4% of hazardous waste being generated. Of this, six studies reported recycling waste and up to 43.9% of waste per procedure was recyclable. Large joint arthroplasties generated the highest amount of recyclable waste per procedure. Three studies investigated carbon emissions from intraoperative consumables, sterilization methods, and through the use of telemedicine. One study investigated water wastage and demonstrated that simple changes to practice can reduce water consumption by up to 63%. The two most common barriers to implementing environmentally sustainable changes identified across the studies was a lack of appropriate infrastructure and lack of education and training.ConclusionEnvironmental sustainability in orthopaedic surgery is a growing area with a wide potential for meaningful change. Further research to cumulatively study the carbon footprint of orthopaedic surgery and the wider impact of environmentally sustainable changes is necessary.Cite this article: Bone Jt Open 2022;3(8):628–640.